2015
DOI: 10.1007/s11092-015-9233-6
|View full text |Cite
|
Sign up to set email alerts
|

Teacher assessment literacy: a review of international standards and measures

Abstract: Assessment literacy is a core professional requirement across educational systems. Hence measuring and supporting teachers' assessment literacy has been a primary focus over the past two decades. At present, there are a multitude of assessment standards across the world and numerous assessment literacy measures that represent different conceptions of assessment literacy. The purpose of this research is to (a) analyze assessment literacy standards from five English-speaking countries (i.e., Australia, Canada, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 25 publications
1
63
0
6
Order By: Relevance
“…However, their feedback practices were found not to develop in alignment with these reshaped conceptions, for the case teachers frequently gave positive but irrelevant feedback on the tasks. Besides, the teachers' CoA changes concerning fairness in classroom assessment and students' involvement in and engagement with assessment are not prominent, although these two assessment dimensions are recognized as key components of classroom assessment theory and practice (Tierney, 2014;Rasooli et al, 2018) and teacher assessment literacy (DeLuca et al, 2016;Xu and Brown, 2016). The insufficient practice during the practicum might mainly account for the misalignment between the teachers' actual feedback practices and their reshaped CoA, as well as for the teachers' partial CoA changes.…”
Section: Diverse But Limited Coa Changes During Practicummentioning
confidence: 99%
See 1 more Smart Citation
“…However, their feedback practices were found not to develop in alignment with these reshaped conceptions, for the case teachers frequently gave positive but irrelevant feedback on the tasks. Besides, the teachers' CoA changes concerning fairness in classroom assessment and students' involvement in and engagement with assessment are not prominent, although these two assessment dimensions are recognized as key components of classroom assessment theory and practice (Tierney, 2014;Rasooli et al, 2018) and teacher assessment literacy (DeLuca et al, 2016;Xu and Brown, 2016). The insufficient practice during the practicum might mainly account for the misalignment between the teachers' actual feedback practices and their reshaped CoA, as well as for the teachers' partial CoA changes.…”
Section: Diverse But Limited Coa Changes During Practicummentioning
confidence: 99%
“…Against the background of the increasing accountability of student learning and the rising importance of assessment for learning across school levels and contexts, there is a pressing need for preparing assessment-literate teachers (DeLuca et al, 2016;Popham, 2018). In China, teachers are placed within tensions between a strong testing tradition that used high-stakes exams for selection and ranking purposes (Carless, 2011;Chen and Brown, 2018) and liberal educational reforms featuring assessment for learning [Ministry of Education of the People's Republic of China (MOE), 2011,2017].…”
Section: Introductionmentioning
confidence: 99%
“…CA researchers have also highlighted the importance of fairness in student-based assessments by publishing a separate chapter on the issue of fairness in the Sage Handbook of Research on Classroom Assessment (2013) and in the Principles for Fair Student Assessment Practices for Education in Canada (Rogers, 1996a(Rogers, , 1996b). These key chapters sit alongside other recent writings in the field to signal increased attention to fairness as a renewed and important construct for 21 st century assessment (Cowie, 2015;DeLuca, LaPointe-McEwan, & Luhanga, 2016;Gipps & Stobart, 2009;Scott, Webber, Lupart, Aitken, & Scott, 2014;Tierney, 2016).…”
mentioning
confidence: 99%
“…Grades, as represented by the grade point average, usually play a critical role in promotion, allocation or selection (Guskey 2007 ). However, aspects of teacher competence (assessment literacy: DeLuca et al 2015 ) and teaching quality (classroom management: Hochweber et al 2014 ) have been shown to increase judgment accuracy and diminish bias in grading. In addition, teachers may use grades to motivate students by rewarding certain behaviors and signaling what attitudes, behaviors and habits are valued in school (OECD 2012 ).…”
Section: Student Assessmentmentioning
confidence: 99%